Mesenteric Cyst of Transverse Mesocolon: A Rare Case Report and Review of Literature - Sunder Goyal; Ram Kumar Verma; Sohan Pal Singh; Mohmad Mozeeb Ahsan (Archives of Clinical and Experimental Surgery, 2013)
Mesenteric cysts are rare and can occur at any age. They are frequently asymptomatic, but sometimes patients may present with an abdominal pain or lump. Mesenteric cysts generally arise within the mesentery of the small bowel in the ileum but rarely in the mesentery of the colon. The exact etiology of mesenteric cysts is unknown. Computed tomography (CT) scanning and ultrasonography (US) are important diagnostic modalities. Surgical removal is the treatment of choice for these lesions. Bowel resection becomes necessary in the event of the gut and the cyst having common blood supply. Once removed, mesenteric cysts rarely recur, and patients have a good prognosis. [Arch Clin Exp Surg 2013; 2(3.000): 200-203]